1994
DOI: 10.1002/tera.1420500309
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral teratologic effects of prenatal exposure to continuous‐wave ultrasound in unanesthetized rats

Abstract: While there are no known risks associated with diagnostic ultrasound, uncertainty about the safety of prenatal ultrasound exposure remains. The purpose of the present experiment was to evaluate the behavioral teratogenic potential of continuous-wave (cw) ultrasound in rats, in the absence of maternal anesthesia or restraint. Pregnant CD rats, trained to remain immobile in a water-filled ultrasound exposure tank, were scanned with 3 MHz cw ultrasound at levels of 0, 2, 10, 20, or 30 W/cm2 ISPTA (spatial peak, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…85 Similarly, reflex activity and behavior in offspring of rats continuously exposed to high-intensity (20 -30 W/cm 2 ) ultrasound were normal except for a small increase in aggregate of errors of commission in the Cincinnati water maze (a neuropsychiatric test for learning behavior). 86 Alterations in adult negative geotaxis and reflex suspension were also observed with exposure to ultrasound. 87 Despite these collective findings, another study found no statistically significant alterations in postnatal behavior or delays in acquisition of reflexes after prenatal ultrasound exposure (less than 1,500 W/cm 2 ).…”
Section: Fetal Effects Of Ultrasoundmentioning
confidence: 89%
“…85 Similarly, reflex activity and behavior in offspring of rats continuously exposed to high-intensity (20 -30 W/cm 2 ) ultrasound were normal except for a small increase in aggregate of errors of commission in the Cincinnati water maze (a neuropsychiatric test for learning behavior). 86 Alterations in adult negative geotaxis and reflex suspension were also observed with exposure to ultrasound. 87 Despite these collective findings, another study found no statistically significant alterations in postnatal behavior or delays in acquisition of reflexes after prenatal ultrasound exposure (less than 1,500 W/cm 2 ).…”
Section: Fetal Effects Of Ultrasoundmentioning
confidence: 89%
“…We used the system to test for teratogenic effects of continuous (Vorhees et al, 1991b) or pulsed ultrasound (Fisher et al, 1993) and in both cases found no teratogenicity in the CWM under standard lighting. We next used the same system to evaluate the neurobehavioral effects of prenatal continuous or pulsed wave ultrasound and again found no effects in the CWM under standard room lighting (Vorhees et al, 1994c; Fisher et al, 1996). …”
Section: Assessing Navigation In Rodentsmentioning
confidence: 99%
“…al. (40) also exposed rats to these levels of ultrasound daily for 10 min on gestational Day 4-20. Although they did not observe exposure-related alterations in maternal parameters, offspring survival and growth, or neonatal psychophysiologic parameters, changes did occur in offspring adult behavior in locomotor activity and in two measures of the multiple-T water maze test performance at the highest dosage level.…”
Section: Discussionmentioning
confidence: 99%